Dynamic properties and strain rate effect of 3D angle-interlock carbon/epoxy woven composites. (October 2017) - Zhao, Jiuzhou; Zhang, Li; Guo, Licheng; Yang, Yongqi
A series of experiments on 3D angle-interlock carbon/epoxy woven composites were carried out using the split Hopkinson pressure bar and split Hopkinson tension bar. These tests were accomplished to investigate the strain rate effect of the dynamic compressive and tensile properties. The strain rate range is about 500/s to 1500/s for through-thickness compressive tests, 150/s to 600/s for in-plane compressive tests, and 600/s to 1000/s for in-plane tensile tests. The corresponding quasi-static properties are given for reference. The tested specimens were observed using optical microscope and scanning electron microscope. The main failure modes of the specimens include fiber breakage, fiber pull out and matrix crack. The compressive modulus of through-thickness direction is positively related to the strain rate. The compressive strength and modulus of in-plane direction shows a light fluctuation within the studied strain rate. It is found that the tensile strength and modulus of in-plane direction are negatively related to the strain rate.